Odpowiedź :
Odpowiedź:
4 i 1/3 - 1 i 3/5 = 4 i 5/15 - 1 i 9/15 = 3 i 20/15 - 1 i 9/15 = 2 i 11/15
1 i 1/2 + 1/6 + 4/9 * 2 i 2/5 = 1 i 3/6 + 1/6 + 4/9 * 12/5 = 1 i 4/6 + 16/15 =
= 1 i 20/30 + 32/30 = 1 i 52/30 = 2 i 22/30 = 2 i 11/15
(3 i 1/15 - 1 i 3/5) * 5 - 2 * 3 i 2/3 + 13 i 2/3 : 5 = (3 i 1/15 - 1 i 9/15) * 5 - 2 * 11/3 + 41/3 * 1/5 = ( 2 i 16/15 - 1 i 9/15) * 5 - 2 * 11/3 + 41/3 * 1/5 =
= 1 i 7/15 * 5 - 2 * 11/3 + 41/3 * 1/5 = 22/15 * 5 - 2 * 11/3 + 41/3 * 1/5 =
22/3 - 22/3 + 41/15 = 0 + 41/15 = 41/15 = 2 i 11/15
Odpowiedź:
a)
4i1/3 - 1i3/5 = 2 + 11/15 (dwie całe i 11/15)
b)
1i1/2 + 1/6 + (4/9)•(2i2/5) = 8 + 1/5 (8 całych i 1/5)
c)
(3i1/15 - 1i3/5)•5 - 2•(3i2/3 )+ (13i2/3):5 = = 2 + 11/15 (2 całe i 11/15)
Szczegółowe wyjaśnienie:
a)
4i1/3 - 1i3/5 = (4 + 1/3) - (1 + 3/5) = (12/3 + 1/3) - (5/5 + 3/5) =
= 13/3 - (8/5) = 13•5/(3•5) - 8•3/(5•3) = 65/15 - 24/15 =
= 41/15 = 30/15 + 11/15 = 2 + 11/15 (dwie całe i 11/15)
b)
1i1/2 + 1/6 + (4/9)•(2i2/5) = 1 + 1/2 + 1/6 +(4/9)•(2 + 2/5) =
6/6 + 3/6 + 1/6 + (4/9)•(10/5 + 2/5) =
= 10/6 + (4/9)•(12/5) = 5/3 + 48/45 = 5•15/3•15 + 48/45 =
= 75/15 + 48/15 = 123/15 =120/15 + 3/15
= 8 + 1/5 (8 całych i 1/5)
c)
(3i1/15 - 1i3/5)•5 - 2•(3i2/3 )+ (13i2/3):5 =
= (45/15 + 1/15 - 15/15 - 9/15)•5 - 2(9/3 + 2/3) + (39/3 + 2/3):5 =
= (22/15)•5 - 2•11/3 + (41/3):5 =
= (22/3 - 22/3) + (41/3)•1/5 =
= (0) + 41/15 = 30/15 + 11/15 =
= 2 + 11/15 (2 całe i 11/15)